A revision of Acrometopia Schiner and closely related genera (Diptera: Chamaemyiidae). - Cogan, Brian H. (Contributions to Entomology = Beiträge zur Entomologie, 1978)
The species of the genus Acrometopia SCHINER; all the New World species previousliy placed in the genius are transferred to the genus Toropamecia gen. nov., with the following new combinations: Toropamecia australis (Malloch), T. maculata (Coquillett), T. punctata (Coquillett) and T. reticulata (Johnson). In addition twelve new species are described. Toropamecia hendeli is proposed as a replacement name for Toropamecia reticulata (Hendel). The genus Parapamecia is erected for a single species Parapamecia intacta spec. nov and a new species Acrometopia setosifrons, from Nepal, is described. Keys a provided to the genera of the tribe Chamaemyiini, and to the species of Acrometopia and Toropamecia. Nomenclatural Acts setosifrons Cogan, 1978 (Acrometopia), spec. n. Parapamecia Cogan, 1978 (Chamaemyiidae), gen. n. Toropamecia Cogan, 1978 (Chamaemyiidae), gen. n. intacta Cogan, 1978 (Parapamecia), spec. n. apaxa Cogan, 1978 (Toropamecia), spec. n. australis (Malloch, 1933) (Toropamecia), comb. n. hitherto Acrometopia australis caribbea Cogan, 1978 (Toropamecia), spec. n. grossa Cogan, 1978 (Toropamecia), spec. n. hendeli Cogan, 1978 (Toropamecia), nom. n. pro Acrometopia reticulata Hendel, 1936, nec Johnson, 1913 hyalipennis Cogan, 1978 (Toropamecia), spec. n. jujuyensis Cogan, 1978 (Toropamecia), spec. n. longipennis Cogan, 1978 (Toropamecia), spec. n. macalpinei Cogan, 1978 (Toropamecia), spec. n. maculata (Coquillett, 1902) (Toropamecia), comb. n. hitherto Acrometopia maculata multipunctata Cogan, 1978 (Toropamecia), spec. n. nigripalpis Cogan, 1978 (Toropamecia), spec. n. punctata (Coquillett, 1902) (Toropamecia), comb. n. hitherto Acrometopia punctata reducta Cogan, 1978 (Toropamecia), spec. n. reticulata (Johnson, 1913) (Toropamecia), comb. n. hitherto Trigonometopus reticulata smithi Cogan, 1978 (Toropamecia), spec. n. veenota Cogan, 1978 (Toropamecia), spec. n.